Dye extracted from Costus woodsonii leave as a natural sensitizer for dye-sensitized solar cell / M.Z. Najihah and Tan Winie - M.Z., Najihah; Tan, Winie (Faculty of Applied Sciences, 2021)
Current work employs dye extracted from leaves of Costus woodsonii as a new sensitizer for dyesensitized solar cells (DSSCs). The leave was extracted in three different solvents namely ethanol, methanol, and acetone. Extraction of leaves was carried out by the freezing method. DSSCs with the configuration of TiO2/dye/electrolyte/Pt were assembled. The dyes in DSSCs were Costus woodsonii leaves extracted in methanol, ethanol, and acetone. DSSC with methanol extract of leaves has an efficiency of 0.23 % and short-circuit current density (Jsc) of 0.63 mA cm-2 . DSSC sensitized with ethanol extract of leaves has an efficiency of 0.37 % and Jsc of 0.85 mA cm-2 . DSSC sensitized with acetone extract of leaves shows the highest efficiency of 0.48 % and Jsc of 1.35 mA cm-2 . The performance of the DSSCs in this work is compared with other natural dyebased DSSCs. The efficiency obtained in this work is better or at par with the works reported by other researchers.